2015
DOI: 10.22487/j25805924.2015.v3.i1.4330
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Kooperatif Tipe Investigasi Kelompok Terhadap Perubahan Konsep Fisika Siswa Kelas Xi Ipa Di Sma Negeri 1 Marawola Pada Konsep Usaha Dan Energi

Abstract: Abstrak - Penelitian ini bertujuan untuk melihat pengaruh model pembelajaran kooperatif tipe investigasi kelompok terhadap perubahan konsep fisika siswa pada konsep Usaha dan energi. Jenis penelitian yang digunakan adalah kuasi eksperimen dengan desain penelitian prates-pascates kelompok kontrol tanpa acak. Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPA SMA Negeri 1 Marawola, dengan sampel penelitian kelas XI MIA 1 sebagai kelas eksperimen dengan jumlah siswa 20 orang, dan kelas XI MIA 2 sebag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Physics studies on work and energy concepts in high school has a wide scope and widely used in everyday life.. The concept of work and energy is complex and abstract because it contains interrelated concepts, so that there are may be misconceptions (Masita et al, 2015). Previous research has revealed that students still have difficulty in understanding the concept of work and energy.…”
Section: Introductionmentioning
confidence: 99%
“…Physics studies on work and energy concepts in high school has a wide scope and widely used in everyday life.. The concept of work and energy is complex and abstract because it contains interrelated concepts, so that there are may be misconceptions (Masita et al, 2015). Previous research has revealed that students still have difficulty in understanding the concept of work and energy.…”
Section: Introductionmentioning
confidence: 99%